The Effect of Direct Learning Models in Improving Mastery of Sepaktakraw Basic Techniques - Hasriwandi Nur; Jonni -; Hilmainur Syampurna (Universitas Negeri Padang, 2019)
The purpose of this study was to determine the effect of direct learning models on the mastery of basic techniques of sepaktakraw students majoring in sports education at the Faculty of Sport Science, Padang State University (FIK UNP). The method of this research is quasi-experimental research with the independent variable direct learning model and the dependent variable is the basic technical ability of sepaktakraw students majoring in sports education FIK UNP. The population in the study were students of FIK UNP. The results showed that there was a significant influence of the direct learning model on the mastery of basic techniques of sepaktakraw students of FIK UNP sports education with a t count of 14.473> t table 2.31 (df 8) with a significance value of 0.000 <0.05. The average pretest score of 13.11 increased at the time of the post test to be 21.11 with an increase of 8 scores (61.02%).